Dating Félire Óengusso: A Review of the Historical Evidence - Volmering, Nicole (Curach Bhán, 2025)
In 1908, following the publication of Stokes’ 1905 re-edition of Félire Óengusso, Rudolf Thurneysen published his well-known critical review of the date of composition of Félire Óengusso. Inspired by Stokes’ change of heart concerning the date of the language and unimpressed by his uncritical use of information from the prefaces, Thurneysen offered an evaluation of the date of the composition of the text based primarily on information concerning historical persons gleaned from the poem’s prologue (THURNEYSEN 1908). His analysis has not gone unchallenged, but has by and large stood the test of time — a testament to Thurneysen’s insightful work. In memory of his legacy, therefore, this article offers a review of the historical evidence concerning the date of Félire Óengusso, addressing also some of the methodological issues behind the scholarly arguments relating to the date.
Colloquium in memoriam Rudolf Thurneysen, 29-31. August 2024, Bonn
IN_PRESS
Hagen
Keywords: Manuscript, Book and Print Cultures; Early Irish texts and literature; Irish History; Medieval Ireland